Evaluation of a chiral cubane-based Schiff base ligand in asymmetric catalysis reactions - Biegasiewicz, Kyle F.; Ingalsbe, Michelle L.; St. Denis, Jeffrey D.; Gleason, James L.; Ho, Junming; Coote, Michelle L.; Savage, G. Paul; Priefer, Ronny (Beilstein Journal of Organic Chemistry, 2012)
Recently, a novel chiral cubane-based Schiff base ligand was reported to yield modest enantioselectivity in the Henry reaction. To further explore the utility of this ligand in other asymmetric organic transformations, we evaluated its stereoselectivity in cyclopropanation and Michael addition reactions. Although there was no increase in stereocontrol, upon computational evaluation using both M06L and B3LYP calculations, it was revealed that a pseudo six-membered ring exists, through H-bonding of a cubyl hydrogen to the copper core. This decreases the steric bulk above the copper center and limits the asymmetric control with this ligand.
Keywords: chiral ligand; cubane; M06L and B3LYP calculations; Michael addition